Perancangan Aplikasi Tes Bahasa Inggris Online (ATBIO) dengan Soal Acak - Hady Pranoto (ComTech: Computer, Mathematics and Engineering Applications, 2011)
English proficiency can be measured through several tests that are recognized internationally like TOEFL. To measure the English proficiency of ‘Binusians’ with TOEFL standards and provide rapid and credible test results, an program design of online English test application (ATBIO) is created by displaying a random question, in which every examinee gets different questions. Prior to the design, first performed profile analysis of the questions in the TOEFL test held by Binus University Language Center. Following is the design of the program using standard UML 2.0 notation. Furthermore, the author submitted the draft to be built by the program developers using java script or ASP. With credible, fast and accurate results of ATBIO, it is expected that people, departments or organizations concerned with these test results can immediately make decisions and take necessary actions.